Use of Physics Forcep Versus Conventional Forcep in Extraction of Mandibular First Molar: Physics Forcep Versus Conventional Forcep - Benazeer; Irshad, Farah; Qadir Khan, Usman; Memon, Zunair Akbar; Kumar Punjabi, Suneel; Ali Zaidi, Syed Aijaz (Pakistan Journal of Health Sciences, 2023)
Dental extractions are common. Atraumatic extractions utilizing various technologies are said to protect paradental structures. The new physics forceps can extract the teeth without stress. Objective: To compare the efficacy of physics versus conventional forcep in extraction of mandibular first molar. Methods: Patients aged 18 t0 40 requiring extraction of mandibular first molar were included in the study. The efficacy of extraction was evaluated based on bone loss, soft tissue tear, time required for extraction, postoperative pains, and root fracture. The participants were divided into two groups (Physics forcep and conventional forcep) using block randomization technique, and the pain and time between both groups were compared using independent samples t-test. Results: The two groups had a mean age of 2.85 ± 0.355 years. Physics Forceps (n=1, 6.7%) caused less soft tissue tears than Conventional Forceps (n=14, 93.3%) (p=0.01). 55.5% of the Physics Forceps group and 44.5% of the Conventional Forceps group took more than 10 minutes to extract (p=0.045). Physics Forceps had a greater rate of complete success (p=0.043) than Conventional forceps (p=0.043). In terms of overall instrument utility, physics forceps scored better than Conventional forces in both good and average scores (p=0.021). The difference in mean pain score in the two groups was statistically significant (p=0.0018) at day 3 and day 7 (p=0.0001) being lower in physic forcep. Conclusions: Physics forceps are a more favorable substitute to traditional forceps for atraumatic tooth extraction.